For a Performance-oriented Notion of Regularity in Inflection: The Case of Modern Greek Conjugation - Stavros Bompolas; Claudia Marzi; Vito Pirrelli; Marcello Ferro; Franco Alberto Cardillo (IJCoL)
Paradigm-based approaches to word processing/learning assume that word forms are not acquired in isolation, but through associative relations linking members of the same word family (e.g. a paradigm, or a set of forms filling the same paradigm cell). Principles of correlative learning offer a set of equations that are key to modelling this complex dynamic at a considerable level of detail. We use these equations to simulate acquisition of Modern Greek conjugation, and we compare the results with evidence from German and Italian. Simulations show that different Greek verb classes are processed and acquired differentially, as a function of their degrees of formal transparency and predictability. We relate these results to psycholinguistic evidence of Modern Greek word processing, and interpret our findings as supporting a view of the mental lexicon as an emergent integrative system.